Alginates as food ingredients absorb extra salt in sodium chloride-treated mice - Yukio Fujiwara; Ryoko Maeda; Hidenori Takeshita; Yoshihiro Komohara (Heliyon, 2021)
Many patients with impaired renal function undergoing dialysis are subject to severe dietary restrictions. Especially overdose of salt is related to crisis of their life, so their meals are basically salt-free or low salt. Therefore, their quality of life is declined due to their yearning for salty taste. In the present study, we searched new salt-adsorbing food materials in dietary fibers to develop food ingredients preventing salt-sensitive hypertension and kidney dysfunction. As a result, calcium alginate and ammonium alginate possessed sodium-binding capacity without releasing potassium which causes a problem in chronic kidney injury. Furthermore, the administration of those fibers inhibited blood NaCl concentration and induced NaCl excretion in mice model.Therefore, calcium alginate and ammonium alginate are new candidate materials as salt-adsorbing materials, thus indicating that the health foods and/or health supplements containing those fibers may be a potentially new tool for prevention of salt-sensitive hypertension and kidney dysfunction.